EFEKTIVITAS EFFLEURAGE MASSAGE UNTUK MENGURANGI NYERI PUNGGUNG PADA IBU HAMIL TRIMESTER III DI RB CI SEMARANG - wulandari, dyah ayu; Andryani, Yuli (STIKES Widya Husada Semarang, 2019)
Background: About 80% of women will feel back pain at some point during pregnancy. Most back pain during pregnancy occurs due to changes in the spinal muscles which are as much as 70%. and 30% of back pain during pregnancy may be due to irregularities in the condition of the spine that occurred earlier.Â Effleurage massage is a form of massage by using a palm that gives a gentle pressure to the top of the body in a circular direction repeatedly.Purpose: Knowing the scale of pain in pregnant women who have back trimester III back pain before and after effleurage massage done at RB CI Semarang.Research methods: Type of research used quantitative method, population in this research is trimester III pregnant woman in RB CI Semarang a number of 40 Respondent with collecting data obtained by doing effleurage massage with pre experimental design using pretest - postest one group design. Sampling technique in this research use Purposive Sampling technique.Results: the results obtained before the effleurage massage performed on pregnant women on average - scale pain 7, while after effleurage massage performed on average pregnant women decreased to pain scale 3. Conclusion:There is effect of effleurage massage on back pain in pregnant mother of trimester III.Keywords: effleurage massage, back painLiterature : 17 (2005 â€“ 2017 )Â AbstractAbout 80% of women will feel back pain at some point during pregnancy. Most back pain during pregnancy occurs due to changes in the spinal muscles which are as much as 70%. and 30% of back pain during pregnancy may be due to irregularities in the condition of the spine that occurred earlier.Effleurage massage is a form of massage by using a palm that gives a gentle pressure to the top of the body in a circular direction repeatedly.Knowing the scale of pain in pregnant women who have back trimester III back pain before and after effleurage massage done at RB CI Semarang.Type of research used quantitative method, population in this research is trimester III pregnant woman in RB CI Semarang a number of 40 Respondent with collecting data obtained by doing effleurage massage with pre experimental design using pretest - postest one group design. Sampling technique in this research use Purposive Sampling technique.the results obtained before the effleurage massage performed on pregnant women on average - scale pain 7, while after effleurage massage performed on average pregnant women decreased to pain scale 3. There is effect of effleurage massage on back pain in pregnant mother of trimester III.Keywords:effleurage massage, back pain